Effect of substituting baking water with brewer's spent grain supernatant on the micro-structure and crumb structure of white wheat flour bread - Van Zyl, Nicola Jean (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScFoodSc)--Stellenbosch University, 2019.